Abundance from Abroad: Migrant Income and Long-Run Economic Development - Khanna, Gaurav; Murathanoglu, Emir; Theoharides, Caroline; Yang, Dean (American Economic Review, 2026)
We study how international migrant income prospects affect long-run development in origin areas. We leverage the 1997 Asian Financial Crisis exchange rate shocks in a shift-share identification strategy across Philippine provinces. Initial migrant income shocks are magnified six-fold over time, increasing domestic income, education levels, migrant skills, and high-skilled migration. Remarkably, 74.9 percent of long-run income gains come from domestic rather than migrant income. Trade driven impacts of exchange rate shocks are orthogonal to effects via migrant income. A structural model reveals that 19.7 percent of long-run income gains stem from educational investments. International migration fosters broad economic development in origin communities. (JEL F22, F31, G01, J24, J82, O15, O16)